Unraveling the Structure of Viral Replication Complexes at Super-Resolution - Linnik, Olga; Liesche, Johannes; Tilsner, Jens; Oparka, Karl (Frontiers in Plant Science, 2013)
During infection, many RNA viruses produce characteristic inclusion bodies that contain both viral and host components. These structures were first described over a century ago and originally termed ‘X bodies’, as their function was not immediately appreciated. Whilst some inclusion bodies may represent cytopathic by-products of viral protein over-accumulation, X-bodies have emerged as virus ‘factories’, quasi-organelles that coordinate diverse viral infection processes such as replication, protein expression, evasion of host defences, virion assembly and intercellular transport. Accordingly, they are now generally referred to as viral replication complexes (VRCs). We previously used confocal fluorescence microscopy to unravel the complex structure of X-bodies produced by Potato virus X (PVX). Here we used 3D-structured illumination (3D-SIM) super-resolution microscopy to map the PVX X-body at a finer scale. We identify a previously unrecognised membrane structure induced by the PVX ‘triple gene block’ (TGB) proteins, providing new insights into the complex interplay between virus and host within the X-body.